2017
DOI: 10.14233/ajchem.2017.20660
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Microbicidal Activity of Substituted 1,2,3-Triazoles having Amide and Hydroxy Functionality

Abstract: Pyrimidines and pyridines are choice for modern day medicinal chemistry. Pyrimidine synthons are synthesized form guanidine and different substituted malonates. One of such pyrimidine ring synthon is 2-amino-5-carboethoxy-4-hydroxy pyrimidine. The commercially deployed synthesis involved a mixture of KOH and guanidine carbonate and gradual temperature controlled addition of diethylethoxy methylene melonate giving a yellow precipitate. The precipitate is cooled to around 5 °C and recrystallized from ethanol-wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…At present, the chemical structure of SDHIs on the market all contain amide bonds, so they are also called amide pesticides. Many studies have shown that amides had broad-spectrum antibacterial, [29][30][31] antiviral, 32 insecticidal 33 and herbicidal 34,35 activities. They were widely used in agricultural production such as methuroxam and fludixamide (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the chemical structure of SDHIs on the market all contain amide bonds, so they are also called amide pesticides. Many studies have shown that amides had broad-spectrum antibacterial, [29][30][31] antiviral, 32 insecticidal 33 and herbicidal 34,35 activities. They were widely used in agricultural production such as methuroxam and fludixamide (Fig.…”
Section: Introductionmentioning
confidence: 99%